Business Intelligence Dashboard Human Resource Capacity to Increase the Capacity City of Bekasi - Prio Pamungkas, R Wisnu; Rakhmi Khalida (Knowbase : International Journal of Knowledge in Database, 2024)
Bekasi City with qualified and evenly distributed human resources will be better able to meet dynamic and complex development needs. Effective data visualization can simplify complex information related to HR capacity, such as education levels, skills distribution, and the number of workers in various sectors, making it easier for policy makers to design strategies including identifying the distribution of filling several positions based on gender and identifying areas of need for educational facilities, children's health, and other infrastructure that supports the growth and development of the younger generation, and developing more effective policies to improve the overall capacity of the city. This research aims to develop a human resource capacity data visualization model as a tool in improving city capacity. This research uses Google Looker Studio as a data visualization platform, data integration is done by Extract, Transform, Load (ETL) method, the data starts from Excel then cleaned, adjusted the format and loaded into Google Sheets. The data used includes key variables that describe the characteristics of human resources in the Bekasi city area, such as education, age group, gender, and demographic distribution. The results show that based on the dashboard visualization, the Bekasi City government can increase 10% representation of the number of women in supervisory and administrator positions in 2 years and the number of only 5% at the S2 or S3 education level requires an increase in education to support the optimization of HR for strategic positions